Paleoamericans in Northeast Argentina - Loponte, Daniel Marcelo (2017)
In this paper, we present a brief synthesis of the record of Fell or Fishtailpoints found in northeast Argentina, including the first two records for Misionesprovince. To date, 11 pieces have been identified in the region, whichdemonstrate techno-morphological similarities with specimens recovered indifferent areas of South America, which are linked to Paleoamerican groups ofthe Pleistocene-Holocene boundary. Although these points are still scarce inthis area, this is probably due to the lack of research and issues related to archaeologicalvisibility. These new records increase the density of findings ofthese early hunter-gatherers on the South American Atlantic slope.